Association of Drinking Water Contamination and Pre-hospital Pharmacological Intervention with Hep E Outbreaks in Children under 12 Years in District East Karachi; A Case Control Study - Saima Manzoor, Geeta Moolchandani, Kiran Khan, Aisha Anis, Muhammad Aitmaud Uddolah Khan, Aftab Hussain Abro (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hepatitis E virus (HEV) remains an important cause of waterborne acute viral hepatitis in low‑resource urban settings. Children are particularly vulnerable in areas where municipal water systems are inadequately treated and prone to faecal contamination. This study assessed the association between municipal drinking water, pre‑hospital pharmacological management, and hepatitis E infection in children under 12 years in District East, Karachi. Methodology: A hospital‑based observational study was conducted among children under 12 years presenting with vomiting and diarrhoea lasting more than 18–24 hours. Of 638 children, 400 with a clear history of consuming water directly from the municipal supply line were selected for testing. Blood samples were analysed by PCR for HEV. Demographic data, drinking water history, and treatment details were recorded. Associations between HEV infection, age group, and water source were analysed using chi‑square tests. Results: Among 400 children tested, 313 (78.25%) were PCR‑positive for HEV. There was a highly significant association between HEV infection and consumption of water directly from the municipal line (p < 0.001). Female children were predominantly affected, comprising 221 (70.6%) of infected cases. Age group was not significantly associated with infection (p = 0.812). Infected children were managed with acetaminophen, oral rehydration, soft diet, and antiemetics as needed. Severely dehydrated cases were admitted; mean hospital stay was 12.13 ± 2.08 days, and all patients survived. Conclusion: The study demonstrates a strong link between unsafe municipal drinking water and paediatric HEV infection, with a notable female predominance but no age‑group effect. Despite substantial burden, supportive management resulted in favourable outcomes. These findings underscore the need to improve urban water safety and strengthen early recognition and basic supportive care for hepatitis E in children. Keywords: Drinking water, Contamination, Hep E, Outbreaks, Children under 12 years, Karachi